REFLECTION OF DEMOCRATIC VALUE AND ATTITUDE OF STATESMAN IN RAJA NEGERI JAMBI AND MENTIKO BETUAH’S FOLKLORE FUNCTION AND STATEMAN - Dian Palupi; Reza Amarta Prayoga (The Republic of Indonesia Defense University, 2020)
Folklore is a construction of local wisdom that grows and develops into the basis of the values of social functions. The social function of the political meaning in folklore can be used as the country’s resilience reflection, like democratic learning and strengthening the figure of the statesman. The social reality that was constructed in folklore can be a gap between the real and imaginary condition in the text. This study dug out the interrelatedness between the reflection of folklore as the forming of the resilience nation’s character and characteristic of Indonesian’s diversity. This study uses a qualitative description method and literature sociology and politic approach. The corpus data are “Mentiko Betuah” (Aceh) and “Raja Negeri Jambi” (Jambi) story. The results of the study indicated that the social reflection of both (stories) can be the basis of the building social resilience to counter radicalism, to grows up tolerances, mutual solidarity, democracy, and the integrity of anti-kleptocratic statesman. The method of the study is a qualitative description. The data of the study are sentences and written expressions in “Mentiko Betuah” (Aceh) and “Raja Negeri Jambi”’s story (Jambi). The results of the study indicated that tolerance and plural values were depicted in “Raja Negeri Jambi” and “Mentiko Betuah” were needed to be maintained. The threat of disintegration of the nation through the inculcation of narrow and shallow ideologies have poisoned people’s perspective, especially millennial society.